An impressive new species of mugadina from queensland with notes on a congeneric species (cicadidae: cicadettinae: cicadettini) - Ewart, A.; Moulds, M.s. (Zootaxa, 2021)
This contribution details the morphology, distribution, and song characteristics of a new grass cicada species within the genus Mugadina Moulds, 2012, previously represented by only two much smaller species. The new species is M. superba sp. n. It occurs widely in central Queensland, occurring in a broad curved zone between the western desert areas and the eastern coast. Details of the morphology and the ticking calling songs presented are given, and detailed comparisons are made of morphology and songs between M. superba sp. n. and M. marshalli (Distant, 1911).